Microwave-assisted sodium alginate extraction from Dictyota menstrualis and the fabrication of green thermal insulators - Abdul Khalil H. P. S.; Abdussalam Giuma; Esam Bashir Yahya; Indra Surya; Arif Nuryawan; Tata Alfatah; Mardiana Idayu Ahmad (eXPRESS Polymer Letters)
This study investigates the enhanced extraction of sodium alginate (SA) from Dictyota menstrualis using microwave-assisted techniques and its subsequent application in fabricating green thermal insulators. Utilizing optimized microwave parameters, we achieved a notable increase in SA yield, peaking at 18.5%, significantly higher than the 14.2% obtained through conventional methods. This process not only underscores the efficiency of microwave-assisted extraction by improving yield by approximately 30% but also highlights its environmental sustainability due to reduced solvent use and shorter processing times. The study demonstrates that increasing sodium alginate concentration from 1 to 5% enhances the mechanical strength and thermal insulation properties of bioaerogel scaffolds, evidenced by an increase in density from 0.171 to 0.234 g/cm3 and a decrease in porosity from 93.6 to 89.6%. Additionally, the thermal conductivity and diffusivity measurements of 0.065 W/(m·K) and 0.294 mm2/s, respectively, affirm the excellent thermal insulation stability of these scaffolds. The study demonstrates the potential of microwave-assisted extraction as a scalable and eco-friendly approach for biopolymer recovery, and the feasibility of using the extracted SA in creating effective, green thermal insulators, marking a significant step towards sustainable material development.